Analysis of charged particle acceleration structures on chips - Krivonosov, G.А.; Vasiliev, A.V. (Problems of Atomic Science and Technology, 2023)
Recently, one of the promising methods of acceleration on diffracted electromagnetic waves is the method of laser acceleration of charged particles on periodic chip structures. The article analyzes the influence of various changes and sizes of chips on the rate of acceleration. Electromagnetic fields formed by dielectric chip structures when irradiated with a laser pulse were calculated using a numerical method. Recommendations are given for choosing the profile of dielectric structures for the purpose of effective acceleration of charged particles. Одним з перспективних методів прискорення на дифракційних електромагнітних хвилях останнім часом є метод лазерного прискорення заряджених частинок на періодичних чіп-структурах. У статті проведено аналіз впливу різних змін та розмірів чіпів на темп прискорення. Чисельним методом прораховані електромагнітні поля, що утворені діелектричними чіп-структурами при опроміненні їх лазерним імпульсом. Надаються рекомендації щодо вибору профілю діелектричних структур з метою ефективного прискорення заряджених частинок.